Synthesis and characterization of biphenylene-containing diazaacenes - Biegger, Philipp; Schaffroth, Manuel; Patze, Christian; Tverskoy, Olena; Rominger, Frank; Bunz, Uwe H. F. (Chemistry - a European journal, 2015)
Abstract We describe the efficient synthesis of substituted benzo[3,4]cyclobuta[1,2-b]phenazine, benzo[3,4]cyclobuta[1,2]benzo[1,2-i]phenazine, and benzo[3,4]cyclobuta[1,2-b]naphtho[2,3-i]phenazine by a condensation reaction of aromatic diamines with the stable biphenylene-2,3-dione.
Gesehen am 25.05.2020